Impact of psycho-educational group intervention using cognitive behavioral therapy on Iranian male drug addicts in a rehabilitation center - Parvizifard, Aliakbar (2012)
This study examined the impact of psycho-educational group intervention using cognitive-behavioral therapy on the level of self-efficacy and motivational readiness for change among the Iranian male drug addicts. The study had an experimental design including an experimental group and a control group. The participants of the study consisted of 75 male drug addicts who were consecutively admitted outpatients in a rehabilitation center. The participants were selected based on inclusion and exclusion criteria of the study and they were randomly assigned into the experimental (n=37) and the control groups (n=38). The groups were compared at pre-test and post-test and the impact of psycho-educational group intervention was also compared after one month follow-up. The participants completed the Iranian version of drug taken confidence questionnaire (DTCQ-IV), the Iranian version of the stages of change readiness and treatment eagerness scale (SOCRATES-IV) as well as urine tests at pre-test, post-test, and follow-up. In the pilot study, the original drug taken confidence questionnaire (DTCQ) and the original stages of change readiness and treatment eagerness scale (SOCRATES) were translated and cross culturally modified into the Persian language and back-translated to English. Results from the pilot study showed that the translated instruments have very high content validity and reliability and that they can be used to measure what they are supposed to measure. For this study, the impact of psycho-educational group intervention was defined by increasing scores in self-efficacy and motivational readiness for change in the experimental group as measured by the pre-test, post-test, and follow-up assessments. The psycho-educational group intervention was presented in 12 sessions; one session per week. The main hypotheses in this study were that there are significant differences in self-efficacy and motivational readiness for change between the experimental and the control groups at the post-test scores. The data were coded and entered into the Statistical Package for Social Science SPSS Ver. 18). The data were analyzed using the repeated measures analysis of variance, as well as the paired and independent samples t-tests. The research findings showed that there were significant differences between the experimental and the control groups with regard to the studied variables, including self-efficacy and motivational readiness for change. The results confirmed all the hypotheses of the study. The results of the study showed that the psycho-educational group intervention applied to the participants in the experimental group was effective and led to significant positive changes in the group. Therefore, based on the results of the study, it can be inferred that the cognitive-behavioral therapy group intervention as a psycho-educational intervention increased self-efficacy and motivational readiness for change in the experimental group. In other words, the research findings showed that after the experimental group received the psychoeducational group intervention, their scores in self-efficacy and motivational readiness for change significantly increased at post-test and follow-up. This implies that the CBT group intervention can be considered an effective approach in the treatment of Iranian male drug addicts. Overall, the results of the present study supported the assumption that the cognitive-behavioral therapy group intervention can have positive benefits in reducing relapse among the Iranian male drug addicts.